El Bitcoin ya no es un valor refugio; The Bitcoin is no longer a safe haven - Raúl Gómez Martínez; María Luisa Medrano García; Eladio Pascual Pedre\~no; Laura Pascual Nebreda (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– Since January 2020, we have been experiencing times of uncertainty and volatility. This study aims to analyze the behavior of cryptocurrencies during periods of volatility and whether they can be considered safe-haven assets. To measure volatility, we utilize the VIX and estimate linear regression models between both variables. The results obtained, using the five most significant non-stable cryptocurrencies, reveal that the three primary ones (BTC, ETH, and BNB) do have a significant relationship with volatility. However, they do not act as safe-haven assets, as they demonstrate a negative correlation during times of uncertainty. The other two cryptocurrencies studied (XRP and ADA) do not exhibit a significant relationship. Given that cryptocurrencies can no longer be considered safe havens, a fact established in various economic literature articles, we analyze the point at which this structural change occurred by examining the correlation between the S&P500 stock index (SPX) and BTC. Employing the Chow test, we find a structural change in 2020. Before 2020, there was no significant correlation between the two variables. However, starting from that year, a positive and significant correlation is observed within a 99 % confidence interval. Studying other cryptocurrencies, including those of smaller size compared to the ones analyzed, could aid in understanding the potential determinants of their behavior. Furthermore, a comparative analysis could be conducted between the behavior of larger cryptocurrencies and those of smaller sizes.
Keywords: G14; 330; Cryptocurrency; volatility; VIX; uncertainty; safe-haven asset